A Bibliography of Works by Dr Maxine K. Rochester. Issue 4 (2nd October 2021) - Gould, C. M.
ABSTRACT: This bibliography of published and unpublished scholarly and industry-based outputs is a summation of the research interests and career trajectory of an Australian LIS academic influential during a time of rapidly changing needs and practice in the library and information management sector and its workforce.